Until death tears us apart: effects of formal home care on spousal health outcomes - Hafe, Francisco Pimentel Branco Von (2020)
The goal of this study is to examine the impact of formal home care on the spousal caregiver’sphysical and mental health. From a sample of 6.136 caregivers, who participated in the SHAREsurvey, 23% received formal home care. This project uses different methodologies: OrderedProbit regressions, Propensity Score Matching, and Fixed Effects estimation. The analysisrevealed that formal home care has no impact on caregiver’s physical and mental health, thatmale caregivers are more likely to benefit from it and seem to have a better overall experience.Also, the health status of the care receivers has a positive impact on caregiver’s health.